Leaf Spray Fertilization of Boron and Zinc on Productivity and Fruit Quality of Japanese Pear Tree - Canesin, R. C. F. S. [UNESP] (2010)
The cultivation of fruit plants from temperate climate in tropical or subtropical regions can be a good income alternative for the producer. However, due to the little existent information about cultivation of those fruit plants, the producers use imported techniques of other producing areas, or even an association of practices used for other fruit plants, pointing out the leaf spray fertilization of micronutrients without appropriate scientific base. In this context, the objective of this study was to verify the effect of the leaf spray fertilization of B and Zn on productivity and fruit quality of Japanese pear tree. The experiment was conducted from 2004 to 2005, in Ilha Solteira, in northwestern Sao Paulo State-Brazil. The climate is, according to the Kopppen Classification, tropical wet and dry (Aw). The 'Okusankichi' cultivar, grafted on Pyrus communis L. rootstock was used as well as doses of 110 g.ha(-1) of B and 250 g.ha(-1) of Zn in each application. The treatments were: T1. water, T2. boric acid, T3. zinc sulfate, T4. T2 + T3, T5. boric acid + urea + citric acid + EDTA, T6. zinc sulfate + urea + citric acid + EDTA, T7. T5 + T6, T8. boric acid + urea + citric acid + EDTA + sodium molibdate + sulfur + calcium chloride, T9. zinc sulfate + urea + citric acid + EDTA + Fe sulfate + Mn sulfate + Mg sulfate and, T10. T8+T9. A randomized blocks design was used and the averages were compared by Tukey test. In the first crop the mixture of boric acid with quelating agents were efficient to supply B to the plants and zinc sulfate plus quelating agents were efficient to increase Zn leaf content. However, the productivity and the fruit quality were not influenced by the leaf spray of B and Zn. In the second crop the leaf content of B and Zn and the productivity were not influenced by the leaf spray; the boric acid and the zinc sulfate with or without quelating agents increased the contents of total soluble solids and, the boric acid with or without quelating agents increased the contents of total titratable acidity.